The effect of critical viewing on the critical writing skills of the translation studies students - Demirbulak, Dilara; Bodur, Kübra (Advances in Social Sciences Research Journal, 2021)
Developing translation students’ critical writing skills is an important issue in academia since they are expected to be critical thinkers and contribute to the field of study. The most important precursor of critical writing is critical reading which is an active, probing, and recursive approach to interpret and use the information and ideas from the text. Meanwhile, keeping in mind the vast explosion of mass media products and technology, critical viewing is unavoidable serving the same purpose of hard-copy texts. Moreover, in recent years, the role of literature as the main component and material of its original texts has accelerated as a teaching of critical thinking and writing rather than a final goal. This paper aims to examine the effect of critical viewing and reading of literary texts on the critical writing skills of undergraduates of the Department of Translation and Interpreting. “Ennis - Weir Critical Thinking Essay Test”, designed by Ennis and Weir in 1985, was used to identify the impact of critical viewing and reading on critical writing skills. In this quasi-experimental study ANOVA, Kruskal- Wallis, and T-test were used to analyze the impact of critical viewing and reading on the critical writing skills of the 30 undergraduates.